NOTARY AUTHORITY IN LEGALIZING FOREIGN PUBLIC DOCUMENTS AFTER ACCESSION TO THE APOSTILLE CONVENTION IN INDONESIA - Ni Putu Winda Adilla Putri; I Wayan Novy Purwanto (Transpublika Publisher, 2024)
This study aims to understand the procedure of legalizing foreign documents in accordance with The Hague Convention on the Abolition of Legalization Obligations for Foreign Public Documents 1961 and analyze the authority of a Notary in legalizing foreign public documents after the issuance of the Presidential Regulation on Ratification of the Convention on the Abolition of Legalization Obligations for Foreign Public Documents 1961. This research uses a normative legal approach with the support of legal concept analysis and regulatory approaches, as well as qualitative analysis techniques through several steps, namely systematization, description, and explanation. The study results show that the legalization of foreign documents in accordance with the Apostille Convention is carried out by eliminating diplomatic or consular legalization procedures and only requires the fulfillment of formalistic requirements stipulated in the Apostille Convention. Regarding the authority of a Notary in legalizing foreign public documents after the issuance of the Presidential Regulation on Access to the Apostille Convention remains in effect and does not reduce the authority of a Notary as stipulated in the Amended Notary Office Law because a Notary is an official appointed to legalize public documents issued or official certificates in accordance with the Apostille Convention.